Proceedings of the 7th International Conference on Nanomanufacturing (nanoMan2021) - Yang, Shuming; Luo, Xichun; Yan, Yongda; Jiang, Zhuangde; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book is a compilation of selected papers from the 7th International Conference on Nanomanufacturing (nanoMan2021), held in Xi$1 (Ban on November 17-19, 2021 after postponing twice due to COVID-19 pandemic. It encompasses the synthesis of nanomaterials, the fabrication of devices, the characterization of various products and systems, process monitoring and quality control, simulations, and the applications of nanoscience and nanotechnologies.s
Advanced Nanomaterials -- Micro/Nanomachining -- Laser Micro/Nano Materials Processing -- Micro/Nanopatterning,Micro-featured Surfaces &Surface Modification -- Micro/Nanoforming -- Process Monitoring and Quality Control -- Modeling & Simulation at Micro/Nano Scale -- Nanoscale,Multiscale Modelling & Analysis -- Nano Characterization and Tools -- Nano/Microsystems &Auto-assembly -- High Precision Machines -- Micro/Nano-electromechanical Systems -- Ultraprecision Manufacturing Systems -- Optical Machining & Measurement -- Atomic and Close-to-atomic Scale Manufacturing (ACSM) -- Other Technologies Associated with Micro/Nano Manufacturing.
Keywords: Nanotechnology; Materials; Nanotechnology; Materials Engineering; Nanomanufacturing -- Congresses; Nanostructured materials -- Congresses; Nanotechnology -- Congresses